Strategi Guru dalam Mengatasi Kejenuhan Belajar Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Peserta Didik Kelas X di MA Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Nisfi Nisa’ul Fitri; Mujiyatun Mujiyatun; Anita Oktavia (Journal on Education, 2024)
This study aims to analyze teacher strategies in overcoming boredom in learning the subject of Islamic Cultural History (SKI) of Class X Students at MA Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung. This type of research uses a descriptive qualitative approach. The data were obtained by observation, interview, and documentation methods. All data were analyzed interactively and continuously, including data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) Teacher Strategies in Overcoming Boredom in Learning the Subject of Islamic Cultural History (SKI) of Class X Students at MA Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung use several strategies that are most often used, namely expository strategies, namely teachers deliver material verbally where the process of speaking orally is the main tool in this strategy, students are expected to be able to master and understand the material delivered by the teacher. (2) The obstacles faced and solutions in implementing Teacher Strategies in Overcoming Boredom in Learning Islamic Cultural History Subjects (SKI) for class X students at MA Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung are that there are still many students who do not understand the material presented by the Teacher so that when the learning process takes place, students tend to be bored and there are still few Teachers in mastering the material so that the delivery of the material is limited. The solution to the obstacles faced is that Teachers need to use other strategies that are more effective in overcoming boredom in the learning process, for example using an inquiry strategy, this strategy emphasizes the process of thinking critically and analytically to find and find answers to a problem that is being questioned, for example, such as questions and answers between teachers and students.